PENGGUNAAN PRINSIP KONSTITUTIF PADA MEREK DALAM PERSPEKTIF TEORI PELINDUNGAN DAN TUJUAN HUKUM - Sudjana Sudjana (Res Nullius Law Journal, 2021)
This study discusses the use of constitutive principles (first to file) on brands based on Act No. 20 of 2016 concerning Trademarks and Geographical Indications in the perspective of protection theory and legal purposes. Research methods used: normative juridical approach, by examining library materials or secondary data through primary legal materials (legislation), secondary legal materials (opinions of legal experts), and tertiary legal materials (dictionaries and other sources); descriptive analysis research specifications; and data analysis is done in a qualitative normative manner. The results of the study showed: (1). The theory of protection that is in accordance with the basis for consideration is issued Law No. 20 of 2016 concerning brands in point a is Public Benefit and Economic Growth Stimulus Theory. But in its implementation, it must be supported by other brands of legal protection theory, namely Reward Theory; Recovery Theory; Incentive Theory; and Risk Theory. (2). The use of constitutive principles (first to file) in brands reflects the legal objectives of "certainty" and means of social change but does not pay much attention to aspects of "fairness" and expediency. "